Analysis on the Effectiveness of Bung Hatta University's Promotion - Linda Wati; Surya Dharma; Purbo Jadmiko (AMAR (Andalas Management Review), 2021)
There has been tight and steep competition in Indonesian universities for prospective students due to the increasing growth of private higher education or universities in all regions. Bung Hatta University as one of the largest universities in the Higher Education Service Institutions (LLDIKTI) region X also faces the impact of this competition. This study aims to analyze and measure the effectiveness of promotions that have been carried out by Bung Hatta University in attracting new prospective students. This research is a descriptive study that aims to describe, explain, and validate research findings. This study found that the main source of information for students obtaining information about Bung Hatta University, including all faculties available, was the nuclear family or close family at 37.99%, the second source of information with a proportion of 19.55% was promotions on social media, internet and websites. Information from students currently studying comes in the third place with a proportion of 12.99%. The fourth place is alumni with a proportion of 8.84% , the fifth place is information from friends or neighbors, as much as 7, 82%, the sixth place is from electronic media at 5.17%, the seventh place is from Senior high school teachers in which the students study 2.09%, the eight source is from the visit of the university promotion team is 1.96%, the ninth source is from mass media, 1.96% and the last one, in the tenth place is information from employees or lecturers of Bung Hatta University is 1.54%. Several factors that encourage students to study at Bung Hatta University are the first one is the image of Bung Hatta University as Higher Education with a proportion of 60.20%, secondly is the economic aspect of 16.62%, the third factor is the student activities with a proportion of 14.11% and the fourth place is the physical aspect with the proportion of 9.08%.